The Discontent of Social and Economic Rights. - Morales, Leticia (Res Publica (13564765), 2018)
One major objection to social rights is a failure of determining which precise social and economic claims should be granted rights status. The social rights debate has grappled with this ‘indeterminacy problem’ for quite some time, and a number of proposals have emerged aimed at fixing the content of these rights. In what follows I examine three distinct approaches to fleshing out the idea of a minimum threshold: social rights as the fulfilment of basic needs, social rights as the securing of a minimally decent life and social rights as a requirement of citizenship (a civic minimum). Each of these proposals progressively expands on what the minimum threshold of social rights requires and, conversely, what obligations they generate on part of the state. I will show that none of these approaches is entirely satisfactory and suggest that the social rights debate look elsewhere to determine its content.